Prenatal risk factors for kidney and urinary tract anomalies - Mak, Robert; Schaefer, Franz (Nature reviews. Nephrology, 2014)
Childhood-onset chronic kidney disease is the result of congenital anomalies of the kidneys and urinary tract in approximately two-thirds of all patients. An area of intense research in recent years, however, is the potential impact of maternal obesity on renal ontogenesis or postnatal renal function in the offspring.
Gesehen am 08.09.2020